Multiple-unit implant frames: one-piece casting vs. laser welding and brazing Sobre estruturas de implantes múltiplos: fundição em monobloco versus soldagem a laser e brasagem - Elza Maria Valadares da Costa; Maximiliano Piero Neisser; Marco Antônio Bottino (University of São Paulo, 2004)
The linear distortion of prostheses over implants, one-piece casting and cast in sections followed by laser welding by laser and brazing was evaluated in an edentulous mandibular model with five parallel abutments, with a distance of 10mm from center to center. Seventy five gold cylinders were tightened with screws on the abutments with 10Ncm torque. The cylinder/analogue assemblies were measured by microscopic examination (0.001mm accuracy) and the obtained results were compared with the GC (control group). Fifteen metal frames were waxed and cast in a gold alloy (Stabilor, Degussa Hulls, Brazil) and divided into three groups with five elements each, as followed: GM (one-piece casting), GB (section and brazing) and GL (section and laser welding). In all groups, measurements were taken at the right, left, buccal and lingual sides of the cylinder/analogue interface and the results were submitted to analysis of variance (ANOVA) and to the Tukey test (5%). The smallest amount of distortion was seen in the laser group (GL with a mean value of 13.58), followed by the brazing group (GB with a mean value of 24.33) and one-piece (GM with a mean value of 40.00). The greatest distortion was found in the one-piece group (GM). A distorção linear das próteses sobre implantes, fundidas em monobloco e fundidas em secções e soldadas a laser e por brasagem foi avaliada em um modelo de uma mandíbula edêntula com cinco análogos de pilares de implantes, paralelos entre si com distância de 10mm medidos de centro a centro. Sobre estes foram parafusados novos cilindros de ouro, com torque de 10N/cm. Então foram executadas 15 sobre-estruturas metálicas que foram divididas: GC - Adaptação passiva dos cilindros de ouro; GM - monobloco, GB - segmentos soldados por brasagem e, GL - segmentos soldados a laser. Observaram-se as estruturas fixadas com parafusos novos sob microscópio de mensuração. A medição foi realizada na vestibular direita e esquerda e da mesma forma na lingual da interface cilindro/análogo e dados anotados em tabela apropriada. Para o eixo y, a técnica de soldagem a laser (Média=12,41 e Dp=11,12) produziu menos distorção significativamente do que a técnica de brasagem (Média=23,06 e Dp=21,88) seguida pela técnica de monobloco (Média=39,83 e Dp=21,88) p=0.05. Para o eixo x, somente o grupo Monobloco apresentou diferença significativa para as demais técnicas (Média=45,66 e Dp=21,56).